Clinical profile and outcome of Dengue fever in Medical Intensive Care Unit of a Tertiary Level Hospital: An Observational Study - Eliza Koirala; Gopendra Prasad Deo; Shital Adhikari; Basanta Gauli; Akriti Bajracharya (Journal of Nepal Medical Association)
Introduction: Dengue fever poses a significant public health challenge in Nepal, with increasingsevere cases requiring intensive care. Limited data exist on the clinical profile and outcomes of critically ill dengue patients in resource-limited settings. This study is aimed to characterize the clinical features, outcomes and complications of dengue patients admitted to a tertiary Intensive care unit in Nepal.